iWazan: A Web Based Application for Arabic Morphological Analyzer - Basyiirah binti Mohd Zawawi; Norasikin Fabil; Nur Syafiqatunnajwa Mohamad Zainol (Penerbit USIM, 2025)
E-Proceedings International Language and Education Innovation Competition 2024 (I-INNOLED 2024) “Navigating The Future of Language And Education In A Transformative Era” 15-16 October 2024 Organized by : Faculty Of Major Language Studies Editors: Lubna Abd. Rahman, Amiliayanti Abd Halim, Maziahtusima Ishak